Contact pattern investigation of gear drives using finite element method - Pintér, Ádám Sándor; Sarka, Ferenc (Design of Machines and Structures, 2022)
This article deals with a study that examines deviations in the curve generated by CAD software and real involutes. As part of this, FEM tests are carried out further from the conclusions drawn from the deviations of the gears created, the purpose is to determine the contact pattern at the design stage. Furthermore, using the results of the studies, we can determine how accurately our results give an accurate picture compared to the result that can be calculated from the theory. Finally, we also test for shafts deformation in the connection of the gears.